The Effect of Profitability, Liquidity, Institutional Ownership, and Managerial Ownership on Capital Structure - Baby Amelia Fransesca S (Pelopor Publikasi Akademika, 2024)
This study aims to obtain empirical evidence on the effect of profitability as measured by Return on Assets (ROA), liquidity measured by Current Ratio (CR), institutional ownership, and managerial ownership on capital structure. The population of this study is companies listed as consumers of the non-cyclical sector on the IDX in 2018-2022, as many as 113 issuers. The method used is a quantitative method with statistical analysis of panel data regression. Capital structure is the dependent variable, and profitability, liquidity, institutional ownership, and managerial ownership are independent variables. The method used is a quantitative method with statistical analysis of panel data regression with the SPSS Analysis tool. Capital structure is a framework that describes how equity and debt are used to finance company operations to generate optimal returns for shareholders and maximize company returns by considering the level of risk. The results showed that partially the Probability (ROA) and Liquidity (CR) were significant to the Capital Structure (DER). Institutional and managerial ownership have no significant effect on the Capital Structure (DER).